2022
DOI: 10.1094/pdis-11-21-2562-re
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth-Promoting Rhizobacteria Promote Growth of Seedlings, Regulate Soil Microbial Community, and Alleviate Damping-Off Disease Caused by Rhizoctonia solani on Pinus sylvestris var. mongolica

Abstract: As the excessive use of chemical fertilizers harms organisms and adversely affects the soil environment, the replacement of chemical fertilizers with biological fertilizers has attracted widespread attention as an environmental protection strategy. In this study, the effects of rhizosphere bacteria inoculation on growth of Pinus sylvestris var. mongolica seedlings, soil parameters, soil microbial community structure, and the biocontrol of damping-off were studied by pot experiments. The results showed that all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Singh et al (2023) showed synergistic effects of various PGPR on the growth promotion of maize. Plant biomass, root parameters and nutrient content of maize plants can be improved significantly by the inoculation of PGPR (Song et al, 2023). An increase in the contents of nutrients, specifically iron and zinc has also been reported in response to the inoculation of PGPR from Bacillus and Paenibacillus species (Ahmed et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al (2023) showed synergistic effects of various PGPR on the growth promotion of maize. Plant biomass, root parameters and nutrient content of maize plants can be improved significantly by the inoculation of PGPR (Song et al, 2023). An increase in the contents of nutrients, specifically iron and zinc has also been reported in response to the inoculation of PGPR from Bacillus and Paenibacillus species (Ahmed et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The most common compounds that take part in biocontrol mechanism include phenazine-1-carboxamide, lipopeptides, 2, 4-diacetylphloroglucinol (DAPG), pyrrolnitrin, pyoluteorin, and phenazine-1-carboxylic acid (PCA). 11 Pseudomonas strains survive well in stress conditions and are very beneficial in the control of several diseases triggered by fungal phytopathogens, 43 mainly damping-off disease caused by Pythium spp., 34 Fusarium solani causing okra root rot, 35 Rhizoctonia solani associated with Rhizoctonia root-rot, 36 and foliage blight disease caused by Phytophthora nicotianae. 37 Plants' ability to defend themselves is strengthened through priming as an adaptive technique.…”
Section: Introductionmentioning
confidence: 99%
“… 11 Pseudomonas strains survive well in stress conditions and are very beneficial in the control of several diseases triggered by fungal phytopathogens, 43 mainly damping-off disease caused by Pythium spp. , 34 Fusarium solani causing okra root rot, 35 Rhizoctonia solani associated with Rhizoctonia root-rot, 36 and foliage blight disease caused by Phytophthora nicotianae . 37 …”
Section: Introductionmentioning
confidence: 99%
“…Currently, polymeric microspheres are mainly used in high performance liquid chromatography (HPLC) as a stationary phase, and their surface is modied with certain functional groups to provide them with certain properties. The common substrates of polymer microspheres are polystyrene (PS), 1 polymethyl methacrylate (PMMA), 2 and poly(glycidyl methacrylate) (PGMA), 3,4 which are widely used in HPLC columns due to their reactivity, low cost, acid and base resistance, and biocompatibility. 5 PS microspheres have good sphericity, high specic surface area, uniform microspheres, controllable particle size, and a very active benzene ring that is reactive to a series of functional groups (e.g., -OH, -COOH, NH, -CHO, etc.).…”
Section: Introductionmentioning
confidence: 99%